La péridurale, un non-choix ? Ethnographie des formes de résistance à une innovation « miracle » - Chiara Quagliariello (Association Anthropologie Médicale Appliquée au Développement et à la Santé, 2021)
In France, where the use of epidural anesthesia is widespread, a significant number of women who do not want to undergo this medical intervention end up having it during childbirth. Based on ethnographic research carried out in a public maternity hospital located in the inner suburbs of Paris, this article focuses, firstly, on the reasons why some women refuse epidural anesthesia. Secondly, the article explores women’s strategies of resistance to epidural anesthesia at two key-moments of their interaction with health professionals : the anesthesia consultations at the eighth month of pregnancy and during labor. Finally, the article underlines the different hardships women must overcome in order to assert their personal choices and shape their childbirth pathway within the hospital setting.